KESEJAHTERAAN PETANI DI DESA BUNTU BATUAN KECAMATAN MALUA KABUPATEN ENREKANG (PERSPEKTIF UNDANG- UNDANG NO 11 TAHUN 2009 TENTANG KESEJAHTERAAN SOSIAL) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This journal aims to describe: 1) A description of the welfare conditions offarmers see the fulfillment of spiritual, material, and social needs inBuntu Batuan Village, Malua District, Enrekang Regency, 2) Efforts made byfarmers in Buntu Batuan Village, Malua District, Enrekang Regency, 3)Challenges and potential of the agricultural sector in Buntu Batuan Village,Malua District, Enrekang Regency. This type of research is descriptivequalitative using a sociological approach through observation, interviews anddocumentation techniques. While the data analysis used is data reduction,data presentation, comparative analysis techniques, and drawing conclusions.The results of this study indicate 1) The welfare of farmers as seen from thefulfillment of spiritual needs, namely the belief in their relationship with thealmighty, which is related to beliefs, values, and beliefs, and material needs,namely the fulfillment of clothing, housing, and food needs and social needswhich are related to individual relationships with the public. 2) In farming, effortsare made on the basis of encouragement from the desire to strive to achievea level of welfare, by seeking additional income by doing work according toability. 3) The challenge in the agricultural sector is when pests and diseases,climate change, and the environment deteriorate. The potential in theagricultural sector is the existence of long-term agricultural products.